Etiological factors in the formation of squamous cell carcinoma - literature review - Sawczuk, Magdalena; Sawczuk, Beata; Miąsko, Agnieszka; Szarmach, Izabela (Journal of Stomatology, 2017)
Squamous cell carcinomas constitute the largest group of upper gastrointestinal tract malignancies. The development of the disease depends on many factors. It usually affects people over 50 years of age, as well as those exposed to numerous carcinogens. The effects of smoking, alcohol abuse, hygienic neglect, nutritional deficiencies and genetic disorders are among the best known. Numerous studies have also confirmed the impact of EBV and HPV infections on the development of malignancies, but research on the viral factor is still ongoing. Aim of the study. To present etiological factors responsible for the development of squamous cell carcinoma of the oral cavity. Materials and methods. A review of the literature from 1990 to February 2017 was performed using the PubMed database with the following keywords: squamous cell carcinoma of the oral cavity, squamous cell carcinoma in the head and neck, etiological factors of squamous cell carcinoma, oncogenic factors, oncogenic viruses and genetic disorders in oral cancers and squamous cell carcinoma. Results. Twelve studies meeting specific criteria for the selection of literature were qualified for the review. The comparative features were defined to find a common denominator of the research results. Discussion. Research aimed at identifying the most common factor leading to oral malignancies is ongoing. Many researchers have identified mucosal exposure to compounds contained in tobacco smoke and alcohol as a primary carcinogen. However, viral infections, most commonly EBV and HPV, as well as hygienic neglect, dietary deficiencies and genetic defects, are equally dangerous carcinogens. The diversity of the cited studies proves the need for the development of modern diagnostic methods and popularization of anti-cancer prophylaxis information. Summary. The oral epithelium is constantly exposed to many harmful factors, including those potentially carcinogenic. The knowledge of the factors that pose a risk of cancer is extremely important because it gives a chance of their quick elimination.